DINAMIKA KAJIAN GENDER DALAM SOSIOLOGI OLAHRAGA DI INDONESIA: SEBUAH TINJAUAN PUSTAKA - Zahra, Regita Cahyani; Hidayat, Mhd. Fadlul; Simatupang, Kristian Kevin Chanra; Hasibuan, Fitri Fadilah; Harahap , Siti Ramalomohati; Siregar , Alfin; Nurkadri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the dynamics of gender studies in the sociology of sports in Indonesia through a literature review approach. Gender issues in sports continue to attract academic attention due to the persistence of inequality, stereotypes, and limited representation of women in various sporting activities. The purpose of this study is to analyze the development of gender discourse within the context of sports sociology in Indonesia. The research employed a qualitative descriptive method using a literature review by examining various scientific publications related to gender and sports published between 2010 and 2025. The findings indicate that gender dynamics in sports are strongly influenced by social construction, cultural values, media representation, and patriarchal perspectives that still position women unequally in the sporting environment.